Effects of water deck on rock blasting performance - Jang, Hyong Doo; Handel, D.; Ko, Y.; Yang, H.; Miedecke, J. (Pergamon, 2018)
Water in the blasthole causes adverse effects on blasting performances, e.g., the incomplete explosion of explosive and toxic fume generation. It is normally pumped out before explosive loading to prevent explosive deterioration. In this study, a new blasting concept – water deck blasting (WDB) is introduced which sealed the water at the blasthole bottom to prevent adverse effects of water as well as maximise the beneficial effect of water on rock breakage performances. A field experiment was conducted in a quarry, bench blasting including twenty-three watery holes among 139 blastholes. Promising results were observed as there was no evidence of toxic fume during blasting and achieved a competent level of fragmentation with even toe-cut at the bottom level. The WBD and a normal charge blast were simulated using ANSYS/AUTODYN and multi-peak oscillations were investigated for the WBD. The advantageous rock breakage performances of the relatively small amount of water rather than the amount of explosive have not been verified but have been discussed referring to the extreme water and the steam explosion phenomenon. The WBD blasting method expects to bring advantageous effects to surface mine blasting.